Effect of Arabic Gum and Xanthan Gum on the Stability of Pesticide in Water Emulsion - Zhang, Xiaoguang; Liu, Jiexiang (Journal of agricultural and food chemistry, 2011)
The effect of arabic gum (AG) and xanthan gum (XG) on the physicochemical properties of 2% pesticide avermyctin in water emulsions was systematically investigated by measuring creaming stability, droplet size, zeta potential, and rheology. Addition of AG and XG had significant influence on the physicochemical properties of emulsions. Emulsions showed high stability throughout the storage time in the AG concentration range of 0−0.14%. In contrast, addition of XG induced the apparent creaming of emulsion as the XG concentration increased from 0.011 to 0.15%, which might be well explained by the depletion flocculation of droplets. The droplet diameter increased progressively with increasing AG concentration; however, it sharply grew initially with XG concentration and reached a maximum, followed by a gradual decrease. Zeta potential increased gradually as AG concentration was lower than 0.081%, followed by a slight decrease, whereas it reduced dramatically as XG concentration increased from 0.011 to 0.040% and then remained almost unchanged. In the AG concentration range of 0−0.14%, the emulsion exhibited typical Newtonian flow behavior and the viscosity decreased a little. The XG emulsion exhibited Newtonian flow behavior at low XG concentrations (≤0.019%), whereas, non-Newtonian flow behavior was displayed at relatively high XG concentrations (>0.019%), wherein viscosity value and yield value increased gradually as XG concentration increased. In addition, the curves of shear stress versus shear rate for XG emulsion and solution were well fitted by a power law model and the Herschel−Bulkley model; the Herschel−Bulkley model fitted much better. The present study would provide useful information for the reasonable application of AG and XG in making stable pesticide emulsion.